2012
DOI: 10.1111/j.1574-695x.2012.00991.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of probiotics, probiotic DNA and the CpG oligodeoxynucleotides on ovalbumin-sensitized Brown-Norway rats via TLR9/NF-κB pathway

Abstract: The aim of the study was to investigate the effect of living probiotics, probiotic DNA and the synthetic oligodeoxynucleotides containing CpG motifs (CpG-ODN) on both immune response and intestinal barrier function in ovalbumin-sensitized rat and the underlying mechanisms. Brown-Norway rats were orally sensitized with ovalbumin, and living probiotics, probiotic DNA extraction, synthetic CpG-ODN or non-CpG ODN control was administered. In the living probiotics, probiotic DNA and CpG-ODN groups, the allergic res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 37 publications
3
19
0
Order By: Relevance
“…Finally, the study of gene expression on intestinal tissue could reflect changes induced locally by oral OVA administration. We found that the gene expression of RMCP-II was significantly increased in FA animals, and these results agree with serum concentrations of this mediator and also with changes reported concerning the gene expression of this molecule in mice and rats with food allergies [ 33 , 35 , 43 ]. However, surprisingly the gene expression of FcεRI did not change with FA induction, although it did after i.p.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Finally, the study of gene expression on intestinal tissue could reflect changes induced locally by oral OVA administration. We found that the gene expression of RMCP-II was significantly increased in FA animals, and these results agree with serum concentrations of this mediator and also with changes reported concerning the gene expression of this molecule in mice and rats with food allergies [ 33 , 35 , 43 ]. However, surprisingly the gene expression of FcεRI did not change with FA induction, although it did after i.p.…”
Section: Discussionsupporting
confidence: 90%
“…In this latter condition, Knippels et al have demonstrated oral sensitization and have evaluated the influence of rat strain [ 30 ] and dosage [ 31 , 32 ]. However, the model of oral sensitization without an adjuvant requires a long process of sensitization (six weeks) and, although it has been used in several studies [ 33 36 ], success after oral sensitization was not always achieved in a high percentage of rats [ 37 ] and/or the sensitization does not always induce the synthesis of IgE antibodies [ 20 , 30 , 38 , 39 ]]. This limitation makes it difficult to use this model for the screening of new therapies or allergenicity studies.…”
Section: Introductionmentioning
confidence: 99%
“…There is some evidence that even non‐viable probiotic bacteria can cause immune modulation in the host (Zhong et al . ). Also, there is very little information regarding possible interactions of strains in multi‐strain formulations; even though some studies in experimental rodents or humans show a synergistic effect on the measured outcome (Baillon et al .…”
Section: Testing Of Microbial Strains For Their Qualifications As Promentioning
confidence: 97%
“…Especially, since TLR activation on IEC affects the mucosal barrier function and potentially shapes mucosal immune responses in the intestine, interactions of allergens with TLR expressed by IEC may facilitate their entry into the gut mucosa and sustain the allergic inflammatory response. Interestingly, treatment with CpG oligodeoxynucleotides improved the intestinal barrier function and increased the percentage of T reg cells in the spleen and MLN (42). Since epithelial TLR may interact with the gut microbiota and luminal antigens, further understanding of the role of epithelial TLR activation in food allergy is necessary.…”
Section: Regulation Of Intestinal Immunity and Tolerance By Tlrs Exprmentioning
confidence: 99%